Improvement of Nasal Obstruction Symptoms after Septoplasty with or without Turbinoplasty - Shafaq Zaman; Saleem Asif Niazi; Shahzad Maqbool; Ayesha Khalid; Yousra Riaz; Muhammad Sulman (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the improvement of nasal obstruction symptoms after septoplasty with or without turbinoplasty. Study Design: Prospective comparative study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, Pakistan, from Jan to Dec 2021. Methodology: Two hundred patients having nasal obstruction due to unilateral deviated nasal septum with contralateral hypertrophied inferior turbinate were included. By convenient sampling, patients were assigned septoplasty with turbinoplasty in Group-A or Group-B. Follow-up was done after 3 and 6 months. NOSE Score was used to evaluate the postoperative effectiveness of the procedures. Results: At three months follow-up, out of 103(51.5%) patients in Group-A, 14(13.59%) were minimally satisfied, 29(28.16%) were moderately satisfied, and 60(58.25%) were totally satisfied with the surgery outcome. Out of 97(48.5%) patients in GroupB, 37(40.66%) were minimally satisfied, 26(26.80%) were moderately satisfied, and 34(35.05%) were totally satisfied. At six months follow-up, in Group A, 9 (8.74 %) were minimally satisfied, 24(23.3%) were moderately satisfied, and 70(67.96%) were totally satisfied with the results. While in group B, 41(42.26%) were minimally satisfied, 21(21.65%) were moderately satisfied and 35(36.08%) were totally satisfied. Conclusion: Patients who underwent septoplasty with inferior turbinoplasty had much higher satisfaction levels than those in Septoplasty alone.